2018
DOI: 10.1111/ipd.12434
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor alpha, growth hormone receptor, and developmental defect of enamel

Abstract: Background Oestrogen (ES) and growth hormone (GH) are hormones that may have a role in caries aetiology and developmental defects of enamel (DDE) since their receptors (ERs and GHR) are expressed during amelogenesis. Aim To evaluate whether genetic polymorphisms in the genes that codify the ERα (ESR1) and GHR are associated with caries experience and DDE in children. Design Two hundred and sixteen children of both genders, aged 9‐12 years, were examined and classified according to caries and DDE phenotype. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
20
1
2
Order By: Relevance
“…It is also possible that tooth size differences among genotypes observed in the present study are mainly due to the effect of oestrogen and its receptors in the enamel. Other studies also supported that oestrogen and its receptors play an important role in enamel development (Arid et al, 2019; Ferrer et al, 2005; Jedeon et al, 2016; Takeshita et al, 2004). Takeshita et al (2004) reported that enamel microhardness is significantly reduced in an animal model as a result of oestrogen deficiency, due to the fact that oestrogen has an important role in influencing the process of enamel and dentin mineralisation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is also possible that tooth size differences among genotypes observed in the present study are mainly due to the effect of oestrogen and its receptors in the enamel. Other studies also supported that oestrogen and its receptors play an important role in enamel development (Arid et al, 2019; Ferrer et al, 2005; Jedeon et al, 2016; Takeshita et al, 2004). Takeshita et al (2004) reported that enamel microhardness is significantly reduced in an animal model as a result of oestrogen deficiency, due to the fact that oestrogen has an important role in influencing the process of enamel and dentin mineralisation.…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies also reported that genetic polymorphisms in oestrogen receptors are involved in developmental enamel alterations. Genetic polymorphisms in ESR1 were associated with dental fluorosis (Dalledone et al, 2019) and with enamel defects (Arid et al, 2019). In the present study, we demonstrated that ESR1 was associated with tooth size of some maxillary and mandibular teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the association between variants of the GHR coding gene and craniofacial tissue phenotypes has been exhaustively addressed [ 4 ]. However, since 2013, new GHR variants, such as P561T, rs6184 SNP and rs6180, have been identified as associated, in one hand, with the face mandibular morphology and tooth dimensions [ 2 , 9 , 86 ] and, in the other hand, with developmental defects of enamel [ 12 ]. Recently Marañón-Vásquez et al showed that genetic polymorphisms in GHR (rs2973015) and IGF2R (rs2277071) have been associated with variations in craniofacial dimensions [ 87 ].…”
Section: Gh/igf Axis Modulates the Morphology Of The Dento-alveolar Complex And Cranio-facial Bonesmentioning
confidence: 99%
“…Recent studies have shown that GHR variants (rs6184 and rs6180) are associated with specific tooth and root dimensions [ 9 , 10 ], as well as with mandibular morphology [ 11 ]. Genetic polymorphisms in GHR (rs1509460) are also associated with developmental defects of enamel arguing for the GHR contribution to dental enamel synthesis and structure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the importance of ERs on cortical and trabecular bone, and also in different bone cell types have been widely explored (42). Although the studied genetic polymorphism rs2234693 and rs9340799 in ESR1 and rs1256049 and rs4986938 were not associated with PAP in the present study, they were previously associated with many different bone conditions (28,43) and oral conditions (43)(44)(45). The genetic polymorphisms rs2234693 and rs9340799 in ESR1 have been largely studied.…”
Section: Discussionmentioning
confidence: 62%